2019
DOI: 10.1590/1806-9282.65.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte and neutrophil to lymphocyte ratios as strong predictors of mortality in intensive care population

Abstract: SUMMARY OBJECTIVE: Patients in intensive care units (ICU) have greater morbidity and mortality. We aimed to study neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in the ICU population. METHODS: Medical and laboratory data of patients treated in ICU were retrospectively analyzed. Patients were divided into deceased and survived groups. RESULTS: The NLR of survived and deceased groups were 3.6 (0.2-31) and 9.5 (1-40), respectively (p<0.001). The PLR of the survived group (111 [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
2
18
0
2
Order By: Relevance
“…However, NLR was associated with mortality in unselected critically ill patients, including sepsis patients 15 . Additional studies have reported that NLR was associated with mortality in patients with sepsis [16][17][18][19][20] . Hwang et al demonstrated that septic shock patients at risk of early death had a low NLR and that late death was associated with an increased NLR 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, NLR was associated with mortality in unselected critically ill patients, including sepsis patients 15 . Additional studies have reported that NLR was associated with mortality in patients with sepsis [16][17][18][19][20] . Hwang et al demonstrated that septic shock patients at risk of early death had a low NLR and that late death was associated with an increased NLR 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Rasio neutrofil limfosit pada semua pasien yang dirawat di ruang ICU meningkat disebabkan karena respons stres peradangan penyakit yang mendasarinya. 9 Pada distribusi subjek berdasarkan jenis kelamin terhadap mortalitas terdapat sebanyak 48,2% subjek yang berjenis kelamin laki-laki dan 51,8% subjek yang berjenis kelamin perempuan pada kelompok yang meninggal, sedangkan terdapat sebanyak 38,6% subjek yang berjenis kelamin lakilaki dan 61,4% subjek yang berjenis kelamin perempuan pada kelompok yang hidup. Pada distribusi subjek berdasar jenis kelamin terhadap rasio neutrofil limfosit, terdapat rerata rasio neutrofil limfosit pada kelompok laki-laki dan perempuan adalah 14,84±11,91 dan 15,09±12,81.…”
Section: Pendahuluanunclassified
“…(AUC: 0,80, p<0,001). 9 Rasio neutrofil limfosit dapat digunakan sebagai penanda inflamasi dalam praktik perawatan intensif karena respons fisiologis leukosit yang bersirkulasi terhadap stres inflamasi menyebabkan peningkatan jumlah neutrofil dan penurunan jumlah limfosit.…”
unclassified
“…It has been suggested that these parameters are associated with the presence and severity of coronary artery disease (CAD) and may predict future coronary events and mortality. [3][4][5][6][7][8][9][10][11] Total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), and ischemia-modified albumin (IMA) are oxidative stress parameters. It has been shown that oxidative stress has an important role in the pathogenesis of atherosclerosis and CAD, and high oxidant levels reflect disease severity and vascular damage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these parameters are associated with the presence and severity of coronary artery disease (CAD) and may predict future coronary events and mortality. 3 –11…”
Section: Introductionmentioning
confidence: 99%